2014
DOI: 10.1016/j.yjmcc.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular myosin modifies in vitro step-size when phosphorylated

Abstract: Cardiac and skeletal muscle myosins have the central role in contraction transducing ATP free energy into the mechanical work of moving actin. Myosin has a motor domain containing ATP and actin binding sites and a lever-arm that undergoes rotation impelling bound actin. The lever-arm converts torque generated in the motor into the linear displacement known as step-size. The myosin lever-arm is stabilized by bound essential and regulatory light chains (ELC and RLC). RLC phosphorylation at S15 is linked to modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 32 publications
9
52
0
Order By: Relevance
“…Step-frequency expectation values for Δ0βmys are statistically equivalent to previous results where the 5 nm step predominates (2, 3). Probability for the 5 nm step increased while probabilities for the 3 and 8 nm steps declined in Δ17βmys compared to Δ0βmys as the fractional contribution from the truncated vELC increased (Figure 3 middle column).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Step-frequency expectation values for Δ0βmys are statistically equivalent to previous results where the 5 nm step predominates (2, 3). Probability for the 5 nm step increased while probabilities for the 3 and 8 nm steps declined in Δ17βmys compared to Δ0βmys as the fractional contribution from the truncated vELC increased (Figure 3 middle column).…”
Section: Resultssupporting
confidence: 82%
“…Step-size values for Δ0βmys are statistically equivalent to previous results (2, 3). We compared 3 step-sizes for the pooled βmys data from Δ0 and Δ17βmys @ 60% (60% truncated) using one-way ANOVA.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Fractional phosphorylation levels of 0, 40%, and 85% (maximally phosphorylated) were investigated. We found that phosphorylation causes a dramatic re-distribution of step-frequencies (Wang et al 2014b). These data are summarized in Table 1 for the 0 (native) and 85% phosphorylated βmys (pβmys).…”
Section: Natural Myosin Activationmentioning
confidence: 88%
“…Muscle myosins produce multiple unitary steps with differing step-sizes necessitating introduction of the relative step-frequency, ω j , for unitary step j (Wang et al 2013b; Wang et al 2014b). It is proportional to the rate of cross-bridge cycling with the higher rate producing a more frequent j th step.…”
Section: In Vitro Step-size and Step-frequency Of Single Myosins In Amentioning
confidence: 99%